102 Real-world Use of Vorasidenib in Adult IDH1/2-Mutant Low-Grade Glioma Across UK NHS Trusts - Abraham Sondhi; Susan Short (Neuro-Oncology, 2026)
Abstract Introduction Vorasidenib is a novel therapy for patients aged ≥12 years with residual or recurrent grade 2 IDH1/2-mutant diffuse glioma. Clinical trials demonstrate reduced tumour growth and improved seizure control without additional neurocognitive toxicity. NICE currently does not recommend routine NHS use due to cost-effectiveness concerns. This study evaluates the practical application, accessibility, and challenges of Vorasidenib across NHS trusts. Method A questionnaire was distributed in February 2025 to UK neuro-oncology centres via the British Neuro-Oncology Society clinical network. Responses assessed usage, patient demographics, treatment protocols, logistical issues, and resource constraints. Data were collected from 30 centres across the United Kingdom, primarily from consultant clinicians. Results Use of Vorasidenib varied. Twenty of thirty centres utilised Vorasidenib in adult patients. Sixteen of these centres followed the standard protocol (40 mg daily, dose reduction for toxicity, liver function and ECG monitoring per managed access guidance), while four centres applied additional criteria, including recent progression and extent of resection. Barriers included clinic capacity, staffing, funding processes, and awaiting NICE guidance. No major safety concerns were reported, and patients highly valued access. Alternative treatments included PCV chemotherapy and standard radiotherapy. Centres with experience highlighted nurse-led clinics to manage intensive monitoring. Regional disparities in access and uncertainty regarding inclusion and exclusion criteria were noted. Conclusions Despite NICE’s current recommendation, Vorasidenib is being used safely within managed access frameworks, with high patient acceptance and manageable operational impact in small cohorts. Wider adoption would require additional resources, standardised MDT processes, and clearer eligibility guidance. These findings provide an early real-world perspective on Vorasidenib use where treatment options remain limited. Acknowledgements The authors acknowledge the contribution of the British Neuro-Oncology Society clinical committee members and participating UK centres.